Optimal bovine collagen concentration to achieve tracheal epithelial coverage of collagen sponges. (14th April 2016) - Suzuki, Ryo; Nakamura, Ryosuke; Nakaegawa, Yuta; Nomoto, Yukio; Fujimoto, Ichiro; Semura, Kayoko; Hazama, Akihiro; Omori, Koichi
Abstract : Objectives/Hypothesis: Artificial tracheas prepared using a collagen sponge and polypropylene mesh have been implanted in patients who received tracheal resections, but epithelialization in the reconstructed area is slow. We determined the optimal bovine atelocollagen concentration necessary for the rapid and complete tracheal epithelial coverage of collagen sponge implants. Study Design: Preliminary animal experiment. Methods: Collagen sponges were prepared using lyophilizing 0.5%, 0.7%, and 1.0% atelocollagen solutions (0.5%, 0.7%, and 1.0% sponges) and were analyzed using scanning electron microscopy. Partial tracheal defects were prepared in rabbits and reconstructed using sponges. Epithelial regeneration in the reconstructed area was evaluated by endoscopic, histological, and scanning electron microscope analyses. Results: All sponges had a membranous structural framework, and numerous fibrous structures filled the spaces within the framework in the 0.5% sponges. The membranous structure in the 0.7% sponges branched at many points, and intermembrane spaces were frequently observed. Conversely, the membranous structure in the 1.0% sponges was relatively continuous, thick, and closely arranged. Two weeks after implantation, tracheal defects were entirely covered with epithelium in two of the four and three of the four of the 0.5% and 0.7% sponge‐implanted rabbits, respectively. The collagen sponges remained exposed to the tracheal lumen in four of the four rabbits in the 1.0% sponge group. Ciliogenesis in the center of the epithelialized region was detected only in the 0.7% sponge group. Conclusion: Collagen sponges prepared from various concentrations of bovine atelocollagen have different structures. Complete epithelial coverage was achieved in more rabbits implanted with sponges prepared using the 0.7% bovine atelocollagen solution than in those implanted with sponges prepared from the 0.5% and 1.0% solutions. Level of Evidence: NA Laryngoscope, 126:E396–E403, 2016